Effect of pharmaceutical pupil dilation using cyclopentolate hydrochloride 1% on intraocular lens power calculation in cataract patients (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: To evaluate the effect of pupil dilation using cyclopentolate hydrochloride1%on ocular biometrics and intraocular lens power calculation using contactultrasonography.Material and methods: In this cross sectional study, biometrics measurements wereperformed 80 eyes of patient with cataract scheduled for cataract surgery at theophthalmology department of tishreen university hospital lattakia from June 2021 toJune 2022 by using contact ultrasonography (AVISO Quantel).The axial length (AL), anterior chamber depth (ACD) mean keratometry (KM) andintraocular lens (IOL) power using SRK/T and Haigis formulas were measured beforeand after instillation of cyclopentolate hydrochloride 1% eye drop. Each parameterwas compared by a paired T student prior to and after papillary dilation and the resultswere analyzed.Results: ACD increased by 3.61% and the difference was statistically significant(P=0.005). while the difference was not significant in AL before and after pupildilation p=0.3 and Km (p=0.80).There is no affect of pupil dilation on Iol power calculation based on SRK/T formulatargeting emmetropia (p=0.05).while using the Haigis formula significantly changedcalculations for emmetropia p=0.008.Conclusion: pupil pharmaceutical dilation using cyclopentolate hydrochloride 1%significantly affect the ultrasonic measurements of ASCD and Iol power calculationusing Haigis formulaKeywords: pupil dilation – Axial length – anterior chamber depth – mean keratometry– Iol power contact ultrasonography – SRT/t formula – Haigis formula.